1969
DOI: 10.1139/o69-152
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of the erythrocyte. XIX. Factors affecting esterification of linoleate by human erythrocytes

Abstract: Factors affecting the esterification in vitro of linoleate-1-14C by intact human erythrocytes were investigated. Lecithin contained the highest proportion of the esterified fatty acid, but it was not possible to detect any incorporation into the neutral lipids. Glucose caused a slight increase in incorporation into erythrocytes which had been stored for 18 h at 4°, but had little effect on fresh cells. Esterification was proportional to the intracellular nucleotide labile phosphate level (corresponding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The data presented here re-emphasize the fact that phthalate esters, commonly used as plasticizers, are biologically active and capable of modifying lipid metabolism in mammalian systems (4)(5)(6)(7)(8)26). The association of phthalate esters with toxicity effects in components of the blood and cardiovascular systems (14,(25)(26)(27)(28)(29)(30) is of particular importance since patients receiving medical treatment with products stored in PVC (polyvinylchloride) plastic containers or PVC plastic delivery devices can be exposed to (10,14,(31)(32)(33)(34), and accumulate phthalates such as DEHP in blood, lung, and myocardium ( 10,14).…”
Section: Heart Mitochondriasupporting
confidence: 60%
“…The data presented here re-emphasize the fact that phthalate esters, commonly used as plasticizers, are biologically active and capable of modifying lipid metabolism in mammalian systems (4)(5)(6)(7)(8)26). The association of phthalate esters with toxicity effects in components of the blood and cardiovascular systems (14,(25)(26)(27)(28)(29)(30) is of particular importance since patients receiving medical treatment with products stored in PVC (polyvinylchloride) plastic containers or PVC plastic delivery devices can be exposed to (10,14,(31)(32)(33)(34), and accumulate phthalates such as DEHP in blood, lung, and myocardium ( 10,14).…”
Section: Heart Mitochondriasupporting
confidence: 60%
“…The data in Table 3 also show that the incorporation of linoleate into reticulocyte lipids was not affected by the elevated levels of ATP. This resembles the picture previously reported for mature erythrocytes (12). In several experiments the level of ATP was lowered to approximately that seen in normocytes by incubation of the reticulocytes without glucose for 4 h. However, there was no significant decrease in the rate of linoleate incorporation (' Table 3).…”
Section: Resultssupporting
confidence: 87%
“…When erythrocytes were incubated with lower concentrations of linoleate such as those used by Shastri and Rubinstin (12) Iysolesithin was found to increase esterifieation. This may be due to alteration s f the membrane by %ysolwithh, allowing penetration' of fatty acids at lower conextratiom.…”
Section: Resultsmentioning
confidence: 86%
“…OLIVEIRA and VAUGHAN (7) and Van DEENEN and coworkers (8,9) noted the incorporation of 14C-labeled fatty acids into washed erythrocyte ghosts in the presence of ATP, CoA and MgCl2. MULDER et al reported an influence of dietary fat (10) on the incorporation of fatty acids into animal erythrocytes and other investigators (11,12) on the im portance of cofactors and nutrients in this phenomenon. This report describes a study of the effect of dietary fat on the lipid composition of sera and erythrocyte in the swine, and the incorporation and release of fatty acids in vitro.…”
mentioning
confidence: 96%